Code-Switching Among Arab Descent and Sundanese Societies - Sa'dudin, Ihsan; Riyadi, Muhsin; Safitri, Eka; Nurhayati, Siti; Taher, Rusdee (Jurnal Al-Maqoyis, 2024)
The purpose of this qualitative case study is to conduct an analysis of the code patterns in verbal communication along with factors of bilingual communication expression. Methods of data collection include notetaking and careful listening to what is being said. Data was analyzed using the steps of data reduction, data display, and conclusion. The findings show that there are 12 patterns of code switching and 7 patterns of code mixing in verbal communication. Factors that contribute to these patterns include the same mother tongue background, the speakers' desire to use correct diction, and the habits and flexibility of speech act participants in communicating. According to the findings, to effectively communicate in a bilingual setting, it is essential to understand both the literal and figurative meanings of the words being used. The scope of this investigation is restricted to language code patterns in preparation for a more exhaustive forthcoming study focusing on the historical linguistics of Arabic usage.